2022
DOI: 10.1017/ash.2021.246
|View full text |Cite
|
Sign up to set email alerts
|

High vaccine effectiveness against coronavirus disease 2019 (COVID-19) and severe disease among residents and staff of long-term care facilities in Norway, November 2020–June 2021

Abstract: Coronavirus disease 2019 (COVID-19) causes high morbidity and mortality in long-term care facilities (LTCFs). COVID-19 vaccine effectiveness against infection was 81.5% and 81.4% among fully vaccinated residents and staff in LTCFs. The vaccine effectiveness against COVID-19-associated death was 93.1% among residents, and no hospitalizations occurred among fully vaccinated staff.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…Past studies of vaccine effectiveness of two doses of mRNA vaccines in long term care populations conducted earlier in the pandemic have reported higher vaccine effectiveness estimates (71-82%) against infection compared with the estimates we observed for fourth doses. 30 31 However, vaccine effectiveness studies conducted later against predominating variants of concern have reported similar estimates to our fourth dose estimates against the omicron variant; two dose vaccine effectiveness against beta infection in long term care facilities in France was 49% and against delta infection in US facilities was 53%. 12 32 Vaccine effectiveness against omicron, particularly against infection, has also been found to be lower than for any previous variant of concern.…”
Section: Discussionsupporting
confidence: 76%
“…Past studies of vaccine effectiveness of two doses of mRNA vaccines in long term care populations conducted earlier in the pandemic have reported higher vaccine effectiveness estimates (71-82%) against infection compared with the estimates we observed for fourth doses. 30 31 However, vaccine effectiveness studies conducted later against predominating variants of concern have reported similar estimates to our fourth dose estimates against the omicron variant; two dose vaccine effectiveness against beta infection in long term care facilities in France was 49% and against delta infection in US facilities was 53%. 12 32 Vaccine effectiveness against omicron, particularly against infection, has also been found to be lower than for any previous variant of concern.…”
Section: Discussionsupporting
confidence: 76%
“…Past studies of 2-dose mRNA VE in LTC populations conducted earlier in the pandemic have reported higher VE estimates (71-82%) than the VE estimates we observed for fourth doses. 32,33 However, VE studies conducted later against predominating variants of concern (VOC) have reported similar estimates to our fourth dose estimates against Omicron; VE against Beta infection in LTC facilities in France was 49% and against Delta infection in United States (US) facilities was 53%. 12,34 VE against Omicron, particularly against infection, has also been found to be lower than any previous VOC.…”
Section: Discussionsupporting
confidence: 79%
“…When booster doses were offered, these could be either of the mRNA vaccines regardless of the vaccine product used for the primary series. Several vaccine effectiveness studies using registry data have been done in Norway, showing good protection against severe disease among the general population as well as specific population groups [7] , [11] , [14] , [15] . In line with other studies, the vaccine effectiveness differed between SARS-CoV variants, effectiveness estimates were higher against more severe outcomes and protection waned with time since last received dose.…”
Section: Introductionmentioning
confidence: 99%